2016
DOI: 10.3389/fnhum.2016.00600
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Anorexia Nervosa: Serotonin Dysfunctions Link Self-Starvation with Body Image Disturbances through an Impaired Body Memory

Abstract: The etiology of anorexia nervosa (AN) is still unclear, despite that it is a critical and potentially mortal illness. A recent neurobiological model considers AN as the outcome of dysfunctions in the neuronal processes related to appetite and emotionality (Kaye et al., 2009, 2013). However, this model still is not able to answer a critical question: What is behind body image disturbances (BIDs) in AN? The article starts its analysis from reviewing some of the studies exploring the effects of the serotonin syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 109 publications
2
35
1
1
Order By: Relevance
“…However, as we have just seen, these different sources are all shaped by the process of predictive multisensory integration. More, we know that different processes (i.e., working memory), neurotransmitters (i.e., serotonin) and brain areas related to multisensory integration (i.e., frontal and parietal lobes) are impaired in individuals with EDs (Gaudio et al, 2016 ; Riva, 2016 ; Brooks et al, 2017 ).…”
Section: Multisensory Impairments In Eating Disordersmentioning
confidence: 99%
“…However, as we have just seen, these different sources are all shaped by the process of predictive multisensory integration. More, we know that different processes (i.e., working memory), neurotransmitters (i.e., serotonin) and brain areas related to multisensory integration (i.e., frontal and parietal lobes) are impaired in individuals with EDs (Gaudio et al, 2016 ; Riva, 2016 ; Brooks et al, 2017 ).…”
Section: Multisensory Impairments In Eating Disordersmentioning
confidence: 99%
“…A perturbations in the dopaminergic reward pathways has been hypothesized to play a role in the AN pathogenesis (Casper, 2006 ; Alcaro et al, 2007 ). Those alteration included reduced Cerebro Spinal Fluid levels of DA metabolites (Kontis and Theochari, 2012 ), functional DA D2 receptor gene polymorphisms (Bergen et al, 2005 ), and increased D2/D3 receptor binding in the striatum (Kaye et al, 2013 ; Riva, 2016 ), indicating an increased D2/D3 densities and a decreased extracellular DA in this region. Moreover, the evidence of a DA imbalance in the ventral striatum in patients with AN, is considered to contribute to anhedonia of feeding behavior, ascetic and anhedonic temperament (Frank et al, 2017 ), as well as dysphoric mood and anxiety (Kaye et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Altered activity in the insula (Kaye et al, 2010 ; Mohr et al, 2010 ; Bär et al, 2013 ; Oberndorfer et al, 2013 ; Strigo et al, 2013 ), abnormalities in the processing of rewards (Bohon and Stice, 2011 ; Avena and Bocarsly, 2012 ; Ritschel et al, 2017 ) and alterations in frontal regions have been reported (Brooks et al, 2011 ; Celone et al, 2011 ; Strigo et al, 2013 ; Kullmann et al, 2014 ). Subsequently, neural models of ED have been developed (Steinglass and Walsh, 2006 ; Brooks et al, 2011 ; Friederich and Herzog, 2011 ; Riva, 2016 ; Steinglass et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The serotonin receptors activated by serotonin—mediating both excitatory and inhibitory neurotransmission—include seven major subtypes, namely 5-HT 1–7 . Moreover, 5-HT 1 receptors include 5-HT 1A , 5-HT 1B , and 5-HT 1D ; also, 5-HT 2 receptors include 5-HT 2A , 5-HT 2B , and 5-HT 2C subtypes (e.g., Riva 2016 ; for a review, see Saulin et al 2012 ).…”
Section: Serotonin 2a Receptor Activation: Hallucinations Mystical Ementioning
confidence: 99%